Synergistical amelioration of muscle atrophy by modulating gut microbiota through the bioconversion of grape seed extract and whey using kefir lactic acid bacteria - Kun-Ho Seo; Eseul Kim; Hyunsook Kim (Future Foods)
Biotransformation of organic compounds through bioconversion could be an effective strategy for improving the gut microbiota and sarcopenia. The effects of bioconversion product (WDG) of wine grape seed flour (G) extract and whey (W) with kefir lactic acid bacteria (D) were evaluated in C2C12 myoblasts and a hindlimb-immobilized mouse model. WDG significantly restored palmitate-induced decreases in myotube length and diameter. C57BL/6 J mice were hindlimb-immobilized for 2 weeks and fed a high-fat (HF) diet with G, W, WG, WD (W + D), or WDG for an additional 5 weeks. Supplementation with WDG synergistically ameliorated immobilization-induced sarcopenia by restoring grip strength, muscle weight, and the expression of genes related to muscle growth markers. Notably, WDG significantly modulated the abundance of butyrate-producing and intestinal barrier function-related gut bacteria, which were significantly and positively correlated with holding impulse and muscle growth markers. In conclusion, the bioconversion of G and W with D may be a useful strategy to establish healthy gut microbiota and prevent sarcopenia.